Case Report: Disseminated Talaromyces marneffei Infection in a Patient With Chronic Mucocutaneous Candidiasis and a Novel STAT1 Gain-of-Function Mutation - Chen, Kuang; Tan, Junfeng; Qian, Shenxian; Wu, Shenghai; Chen, Qiong (Frontiers in Immunology, 2021)
Chronic mucocutaneous candidiasis (CMC) is a disorder of recurrent or persistent chronic noninvasive symptomatic infections of the skin, nails and mucous membranes. This disorder is primarily caused by Candida albicans. Many factors, including primary immunodeficiencies, can make a host more susceptible to CMC. Signal transducer and activator of transcription 1 (STAT1) gain-of-function (GOF) mutations are the most common genetic etiologies of CMC. We describe a case of CMC with disseminated Talaromyces marneffei infection caused by a new pathogenic Y287N mutation at amino acid 287 in the coiled-coiled domain of STAT1, which was identified using whole-exome sequencing. Position 287 might be a hot spot for missense mutations because several amino acid substitutions were found there. Flow cytometry suggested that the Y287N mutation might reduce the expression of IL-17 of Th17 cells in peripheral blood mononuclear cells stimulated by phorbol myristate acetate and ionomycin. The STAT1 Y287N GOF mutation may be the direct cause of recurrent cutaneous and mucosal candidiasis, including the T. marneffei infection in this patient.